Recombinant human mitsugumin 53: a potential therapeutic agent for multiple diseases - Li, Junfeng; Shen, Jingjing; Li, Tian; Wang, Liqun (Frontiers in Pharmacology, 2025)
Mitsugumin 53 (MG53), a member of the tripartite motif family proteins, is predominantly expressed in skeletal and cardiac muscles. Endogenous MG53 was first identified as a crucial component of the sarcolemmal membrane repair machinery. In cardiac muscles, MG53 prevented against ischemia/reperfusion-induced myocardial injury. Recent research has demonstrated that native MG53 is present in and performs significant functions within various non-striated muscle tissues, including lung epithelial cells, the inner cortex of the kidney, macrophages, aortic valves, corneal epithelial cells, as well as in the tear film and aqueous humor. These studies indicate a potential application of recombinant human MG53 (rhMG53) in various disease models. To date, an increasing number of studies have confirmed that rhMG53 exhibits broad protective effects in skeletal muscle injury, cardiovascular diseases, and other multiple-organ injuries. In this review, we clarify the therapeutic functions of rhMG53 and the molecular mechanisms involved in multiple organ injuries, emphasizing the development of rhMG53 protein as a potential therapeutic agent for treating a range of diseases.